Monetary Policy in Transition : The Case of Mongolia - Sloek, Torsten (IMF Working Papers; Working Paper ;, 2000)
This paper analyzes monetary policy in transition. It examines the dynamics of monetary policy in Mongolia using granger-causality tests for monetary variables and inflation. The paper also analyzes money demand using data from 22 Mongolian regions during 1993-1998. The analyses confirm the key role of monetary policy in stabilization and reveal that even in a transition economy as rudimentary as Mongolia, a stable money demand and a predictable relationship between inflation and monetary variables do exist. Hence market-based monetary policy is effective. In addition, the analysis points to a difference between transition and industrial economies in the elasticity of money demand with respect to activity, reflecting the larger role for transactions demand for money.